Dopamine-Mediated Vanillin Multicomponent Derivative Synthesis via Grindstone Method: Application of Antioxidant, Anti-Tyrosinase, and Cytotoxic Activities - Mani A; Ahamed A; Ali D; Alarifi S; Akbar I (Dove Medical Press, 2021)
Arunadevi Mani,1 Anis Ahamed,2 Daoud Ali,3 Saud Alarifi,3 Idhayadhulla Akbar1 1Research Department of Chemistry, Nehru Memorial College (Affiliated to Bharathidasan University), Puthanampatti -621007, Tiruchirappalli District, Tamil Nadu, India; 2Department of Botany & Microbiology, College of Sciences, King Saud University (KSU), Riyadh, Saudi Arabia; 3Department of Zoology, College of Sciences, King Saud University (KSU), Riyadh, 11451, Saudi ArabiaCorrespondence: Idhayadhulla Akbar Tel +91-9994265115Email a.idhayadhulla@gmail.comPurpose: This study aimed to determine the extent of contribution of dopamine to antioxidant and anti-tyrosinase activities, by dopamine addition to vanillin. This study achieved the synthesis of dopamine-associated vanillin Mannich base derivatives prepared via a one-step reaction involving a green chemistry approach, and investigation of antioxidant and anti-tyrosinase activities.Methods: Novel one-pot synthesis of Mannich base dopamine-connected vanillin ( 1a-l) derivatives can be achieved via green chemistry without using a catalyst. Newly-prepared compounds were characterised with FTIR and NMR (1H and 13C) spectra, mass spectra, and elemental analyses. In total, 12 compounds ( 1a-l) were synthesised and their antioxidant and anti-tyrosinase activities evaluated. Antioxidant activities of 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO), hydrogen peroxide (H2O2), and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and diammonium assays, ABTS•+ radical scavenging, and linoleic acid peroxidation were used to screen all synthesised compounds ( 1a-l) for anti-tyrosinase activities and cytotoxicity against MCF-7 and Vero cell lines;.Results: The compound 1k inhibited (IC50:11.02μg/mL) the DPPH-scavenging activity to a greater extent than the standard BHT (IC50:25.17μg/mL), and showed high activity in H2O2 and NO scavenging assays. Compound 1e was more potent (96.21%) against ABTS and compound 1k was more potent (95.28%) against 2,2ʹ-azobis(2-amidinopropane)dihydrochloride antioxidant than the standard trolox. All synthesised compounds were screened for anti-tyrosinase inhibitory activity. Compound 1e had higher activity against tyrosinase (IC50=10.63 μg/mL), than kojic acid (IC50=21.52μg/mL), and was more cytotoxic (GI50 0.01μM) against MCF-7 cell line than the doxorubicin standard and other tested compounds.Conclusion: In this study, all compounds were found to possess significant antioxidant and anti-tyrosinase activities. Compounds 1e and 1k performed well, compared with other compounds, in all assays. In addition, this study successfully identified several promising molecules that exhibited antioxidant and anti-tyrosinase activities.Keywords: Mannich base, grindstone chemistry, antioxidant, anti-tyrosinase activity, cytotoxicity